Efficacy of Pharmacological and Bioactive Compounds on Serum Ovalbumin-Specific Immunoglobulin E and Nasal Symptom Scores in Ovalbumin-Induced Allergic Rhinitis Animal Models: A Systematic Review and Meta-Analysis - Ayunita Tri Wirattami; Iriana Maharani; Edi Handoko; Nanik Setijowati; Shanti Andri Sakarisa (Publikasi Indonesia, 2026)
Allergic rhinitis (AR) is a highly prevalent immunoglobulin E (IgE)-mediated inflammatory disease of the nasal mucosa. Ovalbumin (OVA)-induced AR animal models are widely used to evaluate potential therapeutic agents; however, no quantitative synthesis of treatment effects across pharmacological interventions has been performed. This study aimed to systematically review and meta-analyse the effects pharmacological and bioactive interventions on serum OVA-specific IgE levels, nasal rubbing scores, and nasal sneezing scores in OVA-induced AR animal models. PubMed, EMBASE, Scopus were searched from inception through 22 May 2026. Eligible studies were in vivo experimental studies using OVA-sensitised and intranasally challenged rodent models with at least one pharmacological intervention and an untreated or vehicle control group. Risk of bias was assessed using the SYRCLE tool. Standardised mean differences (SMDs) were pooled using random-effects models with the restricted maximum likelihood (REML) estimator and the Hartung–Knapp–Sidik–Jonkman (HKSJ) adjustment. Analyses were conducted in R using the metafor package. Fourteen intervention studies met the inclusion criteria. Pharmacological and bioactive interventions significantly reduced serum OVA-specific IgE levels (pooled SMD = ?3.03; 95% CI: ?4.77 to ?1.28; I² = 78.1%), nasal rubbing scores (pooled SMD = ?5.24; 95% CI: ?7.17 to ?3.31; I² = 80.2%), and nasal sneezing scores (pooled SMD = ?4.29; 95% CI: ?5.79 to ?2.78; I² = 78.5%). Substantial heterogeneity was observed across all outcomes. Leave-one-out sensitivity analyses confirmed the robustness and directionality of the pooled estimates. Pharmacological and bioactive interventions consistently and significantly attenuated serum OVA-specific IgE levels and nasal symptom scores in OVA-induced AR animal models.